Solvent‐Dependent Bending Ability of Salen‐Derived Organic Crystals. Issue 8 (18th June 2020) - Kusumoto, Sotaro; Saso, Akira; Ohmagari, Hitomi; Hasegawa, Miki; Kim, Yang; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract: The formation of plastic or brittle organic crystals of salen derivatives that depend on the solvents employed for crystallization is demonstrated. Large yellow crystals (ranging from mm to cm size) of ten different salen derivatives were obtained and investigated. Among them, (bis(2‐hydroxyacetophenone)ethylenediimine) 2, which was recrystallized from dichloromethane, tetrahydrofuran or chloroform, exhibited plastic deformation behaviour when mechanical force was applied to the (001) face. In contrast, when 2 was recrystallized from benzene, brittle crystals were obtained. Face indexing confirmed that different crystal faces were obtained by depending on the solvent employed for recrystallization, which leads to either flexible (plastic) or brittle crystals. Photoluminescence with a band maximum at 510 nm and thermochromism related to tautomerism between OH and NH forms were also investigated, and indicate that 2 is a flexible organic single‐crystal material with multifunctional properties. Abstract : Solvent is salient : The formation of plastic or brittle organic crystals of salen derivatives depends on the solvent employed to the recrystallization. The face indexing revealed that different crystal faces are obtained depending on the solvent, resulting in flexible or brittle crystals. The multifunctional nature of salen‐based organic crystals, such as plasticity, fluorescence and thermochromism, is also described.